Facilitating practitioner flexibility within an empirically supported intervention: Lessons from a system of parenting support - Mazzucchelli, Trevor; Sanders, M. (Wiley-Blackwell, 2010)
Reluctance by practitioners to follow manuals is often cited as a reason for the lack of adoption of empirically supported treatments (ESTs). We contend that rigid adherence to the therapeutic techniques described in a manual is neither necessary nor desirable. Rather, practitioners should flexibly deliver interventions to meet the diverse needs of consumers, but in such a way that the intervention is not moved beyond its evidence base. This tension between adherence and flexibility is reframed as an issue of practitioner generalization. The present paper draws on the authors’ experiences from disseminating the Triple P-Positive Parenting Program to describe a number of strategies that can both safe-guard the fidelity with which ESTs are delivered and encourage their flexible delivery.